Edith Wharton, Willa Cather, and the place of culture - Olin-Ammentorp, Julie, 1959- (University of Nebraska Press, 2019)
""Edith Wharton, Willa Cather, and the Place of Culture," the first comparative study of Wharton and Cather in thirty years, combines biographical, historical, and literary analyses with approaches focused on place and on aesthetics to reveal the profound similarities in their theories of fiction, their understanding of human nature, and their concerns about American culture. Employing the dual meanings of both "place" (as location and as status) and "culture" (as general culture and "high" culture), Julie Olin-Ammentorp offers a new view of the resonances between these two authors and their works, focusing on their shared concern about the culture of place and the place of culture in the United States"--